When the woolly rhinoceroses roamed East Asia: a review of isotopic paleoecology of the genus Coelodonta from the Tibetan Plateau to northern Eurasia - Ma, Jiao; Wang, Shiqi; Deng, Tao (Frontiers in Ecology and Evolution, 2024)
East Asia, being the evolutionary center of Coelodonta, offers a unique opportunity to explore the spatiotemporal paleoecologies of this genus. This study utilized bulk and serial stable carbon and oxygen isotope analysis on the Coelodonta nihowanensis and other ungulates from the Longdan fauna as well as two modern goats in the Linxia Basin, aiming to explore the paleoecology of C. nihowanensis at the periphery of the Tibetan Plateau during the Early Pleistocene. The isotopic results of these mammals indicated that C3 vegetation was possibly a major component of the local environment in the Linxia Basin, which was influenced by a seasonal summer monsoon. C. nihowanensis specimens in the Longdan fauna were possibly mixed feeders, as indicated by the wide distribution of their δ 13 C values and the intermediate δ 18 O values compared to other coexisting ungulates. Moreover, the comparison of the δ 13 C and δ 18 O values of similar taxa from the Linxia and Nihewan basins has revealed spatiotemporal differences in the paleoclimate and paleoenvironments of these two regions throughout the Early Pleistocene. This provides a holistic framework for understanding the paleoecology of the C. nihowanensis. The isotopic results of the C. nihowanensis in the Linxia and Nihewan basins suggested varied foraging ecologies across different sites and time spans during the Early Pleistocene. This underscores the adaptability of the C. nihowanensis to diverse environments from west to east in northern China. By scrutinizing the evolutionary ecological history of the woolly rhinoceros from its ancestor, Coelodonta thibetana, to its final form, Coelodonta antiquitatis, this study sheds light on the ecological adaptation of this genus from the Pliocene to Late Pleistocene, spanning its migration from the Tibetan Plateau to northern Eurasia.